A predictive computational model to estimate myocardial temperature during intracoronary hypothermia in acute myocardial infarction. (June 2019) - van Willigen, Bettine G.; Otterspoor, Luuk C.; van 't Veer, Marcel; Rosalina, Tilaï T.; Pijls, Nico H.J.; van de Vosse, Frans N.
Highlights: Study of selective myocardial hypothermia is relevant, because it potentially reduces reperfusion injury due to percutaneous coronary intervention. Verified on porcine data: The numerical model is able to predict myocardial temperature based on arterial temperature. The numerical model is able to predict a realistic myocardial temperature based on arterial temperature for patients. The parameters of the numerical model are within physiological range. The sensitivity analysis reveals an important parameter; therefore, this model is ideal for personalized planning of treatment. Abstract: Hypothermia, if provided before coronary reperfusion, reduces infarct size in animal models of acute myocardial infarction (AMI). Translation to humans has failed so far, because the target temperature is not reached in time within the endangered myocardium using systemic hypothermia method. Hence, a clinically applicable method has been developed to provide intracoronary hypothermia using cold saline, selectively infused locally into the infarct area. In this study, a lumped parameter model has been designed to support the clinical method and to describe this myocardial cooling process mathematically. This model is able to predict the myocardial temperature changes over time, which cannot be measured, based on the temperature and flow of the intracoronary injected cold saline and coronary arterial blood. It was validated using data from an isolated beating porcine heart model and applied on data from patients with AMI undergoing intracoronary hypothermia. In prospect, the computational model may be used as an assistive tool to calculate the patient specific flow rate and temperature of saline required for reliable achievement of the target myocardial temperature in the hypothermia enhanced clinical treatment of AMI.